Dynamic Dependence on ATR and ATM for Double-Strand Break Repair in Human Embryonic Stem Cells and Neural Descendants - Adams, Bret R.; Golding, Sarah E.; Rao, Raj R.; Valerie, Kristoffer (PLOS ONE, 2010)
The DNA double-strand break (DSB) is the most toxic form of DNA damage. Studies aimed at characterizing DNA repair during development suggest that homologous recombination repair (HRR) is more critical in pluripotent cells compared to differentiated somatic cells in which nonhomologous end joining (NHEJ) is dominant. We have characterized the DNA damage response (DDR) and quality of DNA double-strand break (DSB) repair in human embryonic stem cells (hESCs), and in vitro-derived neural cells. Resolution of ionizing radiation-induced foci (IRIF) was used as a surrogate for DSB repair. The resolution of γ-H2AX foci occurred at a slower rate in hESCs compared to neural progenitors (NPs) and astrocytes perhaps reflective of more complex DSB repair in hESCs. In addition, the resolution of RAD51 foci, indicative of active homologous recombination repair (HRR), showed that hESCs as well as NPs have high capacity for HRR, whereas astrocytes do not. Importantly, the ATM kinase was shown to be critical for foci formation in astrocytes, but not in hESCs, suggesting that the DDR is different in these cells. Blocking the ATM kinase in astrocytes not only prevented the formation but also completely disassembled preformed repair foci. The ability of hESCs to form IRIF was abrogated with caffeine and siRNAs targeted against ATR, implicating that hESCs rely on ATR, rather than ATM for regulating DSB repair. This relationship dynamically changed as cells differentiated. Interestingly, while the inhibition of the DNA-PKcs kinase (and presumably non-homologous endjoining [NHEJ]) in astrocytes slowed IRIF resolution it did not in hESCs, suggesting that repair in hESCs does not utilize DNA-PKcs. Altogether, our results show that hESCs have efficient DSB repair that is largely ATR-dependent HRR, whereas astrocytes critically depend on ATM for NHEJ, which, in part, is DNA-PKcs-independent.